Pendidikan Formal Anak dalam Perspektif Nelayan Dusun Ammani Kecamatan Mattiro Sompe Kabupaten Pinrang - Hasriyanti, Hasriyanti; Al Hazar, Badrizal; Al’Ghani, Muhammad Zulfi (Seminar Nasional LP2M UNM, 2025)
Abstract. The quality of human resources is determined by the quality and level of education. The low quality of education causes the quality of human resources to be low which will also affect the management of natural resources, including marine resources. This study aims to describe the condition of formal education, the factors causing the lack of formal education and the efforts made to improve the formal education of fishermen's children in Ammani Hamlet, Mattiro Sompe District. This research is focused in Ammani Hamlet, Mattiro Sompe District, geographically located on the coast of Pinrang Regency. This study used qualitative research methods. Data collection is done through observation, interviews, literature reviews, and documentation. The results showed that the living conditions of the people in Ammani Hamlet were sufficient with the existence of marine resources as natural resources that were used by the community to meet their needs. The livelihood of the people of Ammani Hamlet is very dependent on marine products. The difficult life of the community has resulted in some of their children having to help their parents to go to sea, thus interfering with their learning activities so that in the end they will easily drop out of school. In terms of motivating their children in terms of formal education, it is only a small part because they think that education is not their main goal but how they earn a living for their survival.Keywords: Fishermen, Perspective, Formal Education Children